1991
DOI: 10.1021/bi00230a015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitions of sugar transport produced by ligands binding at opposite sides of the membrane. Evidence for simultaneous occupation of the carrier by maltose and cytochalasin B

Abstract: This study examines inhibitions of human erythrocyte D-glucose uptake at ice temperature produced by maltose and cytochalasin B. Maltose inhibits sugar uptake by binding at or close to the sugar influx site. Maltose is thus a competitive inhibitor of sugar uptake. Cytochalasin B inhibits sugar transport by binding at or close to the sugar efflux site and thus acts as a noncompetitive inhibitor of sugar uptake. When maltose is present in the uptake medium, Ki(app) for cytochalasin B inhibition of sugar uptake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
84
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 7 publications
12
84
1
Order By: Relevance
“…70, No. 1, 1998 KINETICS OF HUMAN BRAIN GLUCOSE UPTAKE 405 carrier (Carruthers and Helgerson, 1991). Furthermore, by comparing our measurements of brain glucose levels over an extended range of plasma glucose levels with those previously reported over a much narrower plasma glucose level range (Gruetter et al, 1992a), we obtained apparent Michaelis-Menten constants Tmax and K, that are in excellent agreement and thus appear to be independent of the range of glucose levels studied.…”
supporting
confidence: 74%
“…70, No. 1, 1998 KINETICS OF HUMAN BRAIN GLUCOSE UPTAKE 405 carrier (Carruthers and Helgerson, 1991). Furthermore, by comparing our measurements of brain glucose levels over an extended range of plasma glucose levels with those previously reported over a much narrower plasma glucose level range (Gruetter et al, 1992a), we obtained apparent Michaelis-Menten constants Tmax and K, that are in excellent agreement and thus appear to be independent of the range of glucose levels studied.…”
supporting
confidence: 74%
“…The inhibitors likely cannot make similar hydrophobic or π-π interactions with Trp388 when the hGLUT transporters are in outward-open conformations because in the outward-open conformation of the closely related hGLUT3, the face of the Trp388 indole ring is inaccessible (14). It is widely accepted that cytochalasin B binds only to inward-open conformations of hGLUT1 (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous biochemical studies have shown that cytochalasin B and forskolin inhibit hGLUT1-mediated sugar transport in RBCs by binding at or close to the hGLUT1 sugar export site (11,12). Recent structural studies on hGLUTs have been focused toward elucidating the glucose-binding site.…”
mentioning
confidence: 99%
“…Several specific inhibitors of glucose transport in cells of eukaryotes have been described. Phloretin, cytochalasin B and maltose have all been shown to inhibit glucose transport in human erythrocytes (Carruthers & Helgerson, 1991). Also, by setting various extracellular glucose concentrations, the glucose transport activity can be specifically modulated.…”
Section: Introductionmentioning
confidence: 99%